Law Number 6 Year 2014 Concerning Village; Opportunities for Institutional Strengthening and the Existence of Village Autonomy - Nasution, Khoiruddin; Nasution, M. Arif; Sihombing, Marlon; Kusmanto, Heri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The regulation of village existence through Law no. 6 of 2014 must be acknowledged as providing opportunities for the growth of village autonomy. A number of pressures in several articles provide discretion that allows village autonomy to grow along with several conditions that must be considered by the village government, village communities. UU no. 6 of 2014 at least encourages its autonomy to make all affairs that have been recognized and respected by the state, plus local scale affairs not just for display, but the accumulation of all assets that allow the village to get richer with the capital it has. This research uses a qualitative approach with case studies as a research strategy. Data were obtained from interviews and Focus Group Discussions (FGD) by presenting key informants and also supporting informants from the village government, community leaders and also traditional and religious leaders in Padangsidempuan City. The concept of village development, known as bottom-up development, places the village as a pillar of national economic development. This concept then forces the village to continue to prepare itself in order to achieve village autonomy and independence. Institutional strengthening can be seen from community institutions being given space in planning and implementing development in the village. This shows that Law no. 6 of 2014 has provided space for the community in determining the direction of village development.